2016
DOI: 10.1128/iai.01325-15
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Five Genes Encoding Uncharacterized Proteins Inhibits Entamoeba histolytica Phagocytosis of Dead Host Cells

Abstract: Entamoeba histolytica is the protozoan parasite that causes invasive amebiasis, which is endemic to many developing countries and characterized by dysentery and liver abscesses. The virulence of E. histolytica correlates with the degree of host cell engulfment, or phagocytosis, and E. histolytica phagocytosis alters amebic gene expression in a feed-forward manner that results in an increased phagocytic ability. Here, we used a streamlined RNA interference screen to silence the expression of 15 genes whose expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Our observations indicate that EhAGCK1 is recruited after EhAGCK2, which is similar to the sequential recruitment of PKCε and PKCα during FcγR-mediated phagocytosis 36 . EhAGCK1 may play a role in downstream signalling necessary for formation of initiation complexes, which may include membrane-remodelling molecules such as BAR domain-containing proteins that have been shown to be associated with phagocytosis and virulence 37 . In contrast, in case of phagocytosis of pre-killed CHO cells, only EhAGCK2 is recruited to the phagocytic cups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations indicate that EhAGCK1 is recruited after EhAGCK2, which is similar to the sequential recruitment of PKCε and PKCα during FcγR-mediated phagocytosis 36 . EhAGCK1 may play a role in downstream signalling necessary for formation of initiation complexes, which may include membrane-remodelling molecules such as BAR domain-containing proteins that have been shown to be associated with phagocytosis and virulence 37 . In contrast, in case of phagocytosis of pre-killed CHO cells, only EhAGCK2 is recruited to the phagocytic cups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7B ). Furthermore, since cell killing appears to be the rate-limiting step in rapid phagocytosis of viable cells ( 28 ), we assayed phagocytosis of apoptotic cells and again found no significant difference ( Fig. 7C ).…”
Section: Resultsmentioning
confidence: 83%
“…Given the known roles of actin polymerization in amoebic adherence and phagocytosis and that EhCoactosin localizes within phagocytic cups and its overexpression reduced phagocytosis by ∼50% in a prior report ( 20 ), it is somewhat surprising that adherence and phagocytosis were not significantly affected by Coac-A and Coac-D overexpression. Furthermore, although cell killing was not directly assayed, we note that cell killing is the rate-limiting step in phagocytosis ( 28 ); thus, the absence of an effect on phagocytosis of viable cells suggests that cell killing is also unaffected by expression of these protein constructs. As noted above, a limitation of this experimental system is the ongoing expression of the genomic copy of the EhCoactosin gene, which might cause false-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, presence of these proteins in amoeba is an interesting avenue. A study reported that silencing of EhBAR (C4M128) impacted phagocytosis by the amoebic trophozoites, 101 further strengthening the implications of this domain in actin regulation.…”
Section: Resultsmentioning
confidence: 87%
“…ENTH domain containing proteins are functionally involved in actin regulation 119 . C4M9B6 was shown to be an important protein during phagocytosis 101 . C4LYB3 (1623 aa.)…”
Section: Resultsmentioning
confidence: 99%